2022
DOI: 10.1088/2057-1976/ac7f39
|View full text |Cite
|
Sign up to set email alerts
|

Safety of arterial shear wave elastography–ex–vivo assessment of induced strain and strain rates

Abstract: Shear wave elastography (SWE) is a promising technique for characterizing carotid plaques and assessing local arterial stiffness. The mechanical stress to which the tissue is subjected during SWE using acoustic radiation force (ARF), leading to strain at a certain strain rate, is still relatively unknown. Because SWE is increasingly used for arterial applications where the mechanical stress could potentially lead to significant consequences, it is important to understand the risks of SWE- induced strain and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…ARFI pushes that generate shear waves for SWE typically require longer pulse durations and higher pressures compared to conventional B-mode ultrasound imaging. Therefore, it is important to consider the biosafety aspects of SWE ( 32 ). In general, the biosafety of SWE should meet the same criteria as conventional B-mode ultrasound imaging.…”
Section: Discussionmentioning
confidence: 99%
“…ARFI pushes that generate shear waves for SWE typically require longer pulse durations and higher pressures compared to conventional B-mode ultrasound imaging. Therefore, it is important to consider the biosafety aspects of SWE ( 32 ). In general, the biosafety of SWE should meet the same criteria as conventional B-mode ultrasound imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Doherty et al showed increased SWE displacements in regions identified as lipid on MRI, while Huang et al suggested that larger local deformations and increased complexity in deformation patterns are more likely to occur in vulnerable plaques [ 121 , 122 , 123 ]. Using histology as the reference method, Czernuszewicz et al showed increased diagnostic accuracy of elastography when fibrous cap thickness was included in the measurements, with smaller thickness associated with higher rupture risk at a cut-off value of 0.5 mm [ 124 ]…”
Section: Elastography Of Carotid Atherosclerotic Diseasementioning
confidence: 99%